BRICS' scientific excellence and the search for relevance and replicability - Vílchez‐Román, Carlos (2016)
JASIST recently published a brief communication focused on two dimensions of scientific production: excellence (top 10% and top 1% highly cited publications) and international collaboration (measured by coauthorship networks) of BRICS’s scholar publications (Bornmann, Wagner, & Leydesdorff, 2015). The authors used data from the Max Planck Digital Library, an in-house version of the Web of Science (WoS). Although their bibliometric analysis for data is detailed, three issues are discussed here: replicability, relevance for national research agendas, and contextualization